KAJIAN IP VIRTUAL (VIRTUAL SERVER) TERHADAP KEAMANAN JARINGAN - Felix Wuryo Handono (LPPM Universitas Bina Sarana Informatika, 2016)
The large number of Internet users has made the business people expand their business network with a wide variety of products or packages offered to the users of Internet services. Including, network security systems and infrastructure, hire a data center with costs less Infrastructure financing, easier management of servers in the cloud, DRC (Disaster Recovery Center), ease of backup server in the event of a crash or constraints, and much more. The rapid growth of the internet industry in addition to increasing competition among businesses has also become the target of the search for security holes such data retrieval, data of customers or transactions, vandalism system to network flooding. Good anticipation needed to handle various security problems mentioned above. Utilization of the network infrastructure configuration using virtual IP can be used to reduce one of securities gap.